2009
DOI: 10.1007/s11422-009-9212-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between science and religion in the education of protestant biology preservice teachers in a Brazilian university

Abstract: In this paper we discuss the results of an investigation aiming at mapping the conceptions of nature of protestant biology preservice teachers in a Brazilian university, State University of Feira de Santana, and elucidating their strategies to manage the coexistence of scientific and religious knowledge. We employ naturalistic semi-structured interviews about conceptualizations of nature to build first person interpretive narratives, which allow us to build a general characterization of the students' conceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 9 publications
1
8
0
7
Order By: Relevance
“…Nevertheless, concerning the Protestant teachers in South Korea, the religion effect is here more important than the country effect. Fundamentalist Protestants seem to have the same characteristics across different countries, that we also observed for instance in Brazil (for Protestant pre-service teachers in Brazil, see also El Hani & Sepulveda, 2010), and that are regularly mentioned in the research done in US on acceptance of evolution by the total population or by the students (Baudouin & Brosseau, 2013;Forrest & Gross, 2004;Gould, 1983Gould, , 2000Lecourt, 1992;Miller et al, 2006;Numbers, 2006).…”
Section: Discussionsupporting
confidence: 74%
“…Nevertheless, concerning the Protestant teachers in South Korea, the religion effect is here more important than the country effect. Fundamentalist Protestants seem to have the same characteristics across different countries, that we also observed for instance in Brazil (for Protestant pre-service teachers in Brazil, see also El Hani & Sepulveda, 2010), and that are regularly mentioned in the research done in US on acceptance of evolution by the total population or by the students (Baudouin & Brosseau, 2013;Forrest & Gross, 2004;Gould, 1983Gould, , 2000Lecourt, 1992;Miller et al, 2006;Numbers, 2006).…”
Section: Discussionsupporting
confidence: 74%
“…That is, presenting scientific knowledge as the ultimate truth to replace religious beliefs about matters such as human evolution and homosexuality may lead to the rejection of science altogether. As prior studies have shown, many teachers in religious societies tend to undermine or de-legitimize scientific knowledge which are perceived to conflict with religious faith (Croché, 2015;El-Hani & Sepulveda, 2010;Mansour, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies confirm and further illuminate the influence of teachers' religious views on their teaching. An interview-based study conducted in a Protestant context (Brazil) found that pre-service teachers differed in how they negotiate tensions between their religious and scientific knowledge (El-Hani & Sepulveda, 2010). Some pre-service teachers recognize that religious knowledge is as epistemologically distinct from scientific knowledge, and thus can see them as serving different facets of the human needs.…”
Section: Religious Beliefs and Science Educationmentioning
confidence: 99%
“…Tanto o estudo sobre a origem do universo, quanto estudos envolvendo a origem e evolução da vida permitem o engajamento em diálogos construtivos com as crenças de estudantes que podem entrar em conflito com teorias científicas (SHIPMAN et al, 2002;HANSSON;REDFORS, 2006;SEPÚLVEDA, 2010;EL-HANI, 2013 Em suma, toda sorte de discussões e questionamentos que nos façam refletir sobre o que é o conhecimento científico e como ele é produzido não devem ficar distantes da escola.…”
Section: Origens Da Vidaunclassified